Dentin remineralization via adhesive containing amorphous calcium phosphate nanoparticles in a biofilm-challenged environment. (October 2019) - Tao, Siying; He, Libang; Xu, Hockin H.K.; Weir, Michael D.; Fan, Menglin; Yu, Zhaohan; Zhang, Min; Zhou, Xuedong; Liang, Kunneng; Li, Jiyao
Abstract: Objectives: The remineralization of dentin at a bonded interface would help to strengthen the bonded interface and inhibit secondary caries, and would prolong the longevity of restoration. The aim of this study was to investigate the remineralization of demineralized human dentin in a dental biofilm environment via an adhesive containing nanoparticles of amorphous calcium phosphate (NACP). Methods: Dentin demineralization was promoted by subjecting samples to a Streptococcus mutans acidic biofilm for 24 h. Samples were divided into a control group, a commercial fluoride-releasing adhesive group, and an NACP adhesive group. All samples were subjected to a remineralization protocol consisting of 4-h exposure per 24-h period in brain heart infusion broth plus 1% sucrose (BHIS) followed by immersion in artificial saliva for the remaining period. The pH of BHIS after 4-h immersion was measured every other day. After 10 days, the biofilm was assessed for colony-forming unit (CFU) count, lactic acid production, live/dead staining, and calcium and phosphate content. The mineral changes in the demineralized dentin samples were analyzed by transverse microradiography, hardness measurement, X-ray diffraction characterization, and scanning electron microscopy. Results: The NACP adhesive achieved acid neutralization, decreased biofilm CFU count, decreased biofilm lactic acid production, and increased biofilm calcium and phosphate content (P < 0.05). The NACP adhesive group had higher remineralization value than the commercial fluoride-releasing adhesive group (P < 0.05). Conclusions: The NACP adhesive was effective in remineralizing dentin lesions in a biofilm model. Its ability to protect bond interface, inhibit secondary caries, and prolong the longevity of restoration is promising. Clinical significance: Using NACP-containing adhesives could be recommended because of the protective ability of its hybrid layer even under a biofilm-challenged environment.